Identity status development in the South African context : Relations with defenses, narcissism, parental attachment and ego strengths - Mashegoane, Solomon (University of Limpopo (Turfloop Campus), 2012)
The identity status paradigm (ISP) is probably the most common theoretical model used to study identity development. It originates from Erikson’s (1950/1977) psychosocial theory, which, in turn, is historically rooted in the psychoanalytic perspective. The ISP postulates predictable relationships between each of the identity status categories and various intrapersonal and contextual variables. The applicability of the ISP in the South African context is tested in this study. A student sample was drawn from a predominantly African university, and was assessed for identity development over a period of three consecutive years (Ns = 394, 96 & 60, for years one, two and three, in that order). Participants were initially classified into the four identity status categories of Achievement, Moratorium, Foreclosure and Diffusion. The impact of gender and age on identity status development was investigated. The association between defenses and the identity statuses was also determined. Thereafter, identity statuses, in conjunction with defenses, narcissism, and parental attachment, were related to the ego strengths of Fidelity and Love. The results suggest that generally there is no relationship between the sets of variables in this particular sample. The results are discussed in relation to existing literature, and the issue of the appropriateness of the theory and/or the measures in the present sample is raised. Key terms: defense, ego strength, identity status, narcissism, parental attachment
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2012
Keywords: Identity status development; Narcissism; Parental attachment; Ego strengths; 155.2; Identity (Psychology); Narcissism; Sex differences